Virus-templated Au and Au/Pt Core/shell Nanowires and Their Electrocatalytic Activitives for Fuel Cell Applications - LEE, YOUJIN (2012)
A facile synthetic route was developed to make Au nanowires (NWs) from surfactant-mediated bio-mineralization of a genetically engineered M13 phage with specific Au binding peptides. From the selective interaction between Au binding M13 phage and Au ions in aqueous solution, Au NWs with uniform diameter were synthesized at room temperature with yields greater than 98 % without the need for size selection. The diameters of Au NWs were controlled from 10 nm to 50 nm. The Au NWs were found to be active for electrocatalytic oxidation of CO molecules for all sizes, where the activity was highly dependent on the surface facets of Au NWs. This low-temperature high yield method of preparing Au NWs was further extended to the synthesis of Au/Pt core/shell NWs with controlled coverage of Pt shell layers. Electro-catalytic studies of ethanol oxidation with different Pt loading showed enhanced activity relative to a commercial supported Pt catalyst, indicative of the dual functionality of Pt for the ethanol oxidation and Au for the anti-poisoning component of Pt. These new one-dimensional noble metal NWs with controlled compositions could facilitate the design of new alloy materials with tunable properties.